KETELADANAN DALAM PANEMBROMO DI DESA LANGSUR KABUPATEN SUKOHARJO JAWA TENGAH - Jumanto Antrop (MADROSATUNA : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2019)
Considering the importance of local culture role in shaping citizens’ personality and character, this research aims to analyze the values of panembromo. This research uses qualitative approach, data collection techniques using observation, interviews, study documents, and field notes. Data analysis techniques use hermeneutic analysis. The results showed that the dominant value contained in panembromo is exemplary. Exemplary value is seen on the activity of panembromo actors. The exemplary value has the potential to be implemented in school education.